Governance of Public Broadcasters and Television Consumption - Christine Benesch (Center for Research in Economics, Management and the Arts (CREMA), 2010)
Recent literature emphasizes the importance of independent media for beneficial political, economic and social outcomes. I investigate how media consumers react to state ownership of TV stations and the regulation and financing of these public broadcasters. The empirical results show that a higher share of state-owned TV stations is associated with lower TV consumption, both in total and with regard to news and information only. The negative effects of state ownership are larger when the public stations are regulated by a Ministry as opposed to a more independent regulatory body. When public broadcasters are subject to selfregulation only, there is even a positive association between the share of state ownership and TV consumption. The negative effects of state ownership and total TV consumption A but not news and information consumption A are also smaller when the share of commercial income of public broadcasters is higher. The results are consistent with the view that political influence leads mainly to less attractive news information broadcasting whereas public funding leads to a less attractive entertainment spectrum but not to less attractive news.
Keywords: L82; H41; L51; D83; 330; Media consumption; television; public service broadcasters; regulation; state ownership